What Norman Saw in the West - Olin, Julia M. (Julia Matilda), 1814-1879 (Salt Lake City, UT : Project Gutenberg, 2018)
"What Norman Saw in the West" by Julia M. Olin is a fictional narrative written in the mid-19th century. The story follows a young boy named Norman Lester, who embarks on a journey with his mother to the American West, where they explore iconic landmarks such as Niagara Falls and the Mississippi River. Throughout their travels, they encounter various landscapes, meet new people, and reflect on deeper themes of life and human experiences. The opening of the book introduces Norman and his mother as they prepare for their journey from Broadway to the West, highlighting the beauty and tranquility of the early morning city. As they board a train, Norman is filled with excitement about the adventures ahead, longing to evolve and grow from the trip. The initial chapters vividly describe their travels, experiencing the stunning scenery along the way, from lush prairies to majestic waterfalls, setting the stage for reflections on nature and the human spirit. The narrative establishes Norman$1 (Bs character as curious and impressionable, showcasing his interactions with family and the thoughts that arise from the breathtaking vistas they encounter, paving the way for further adventures. (This is an automatically generated summary.)s
Release date is 2018-09-06
Richard Tonsing and the Online Distributed Proofreading Team
Keywords: Christian life -- Juvenile fiction; United States -- Description and travel -- Juvenile fiction